Architectures for next generation high throughput satellite systems. (27th January 2016) - Vasavada, Yash; Gopal, Rajeev; Ravishankar, Channasandra; Zakaria, Gaguk; BenAmmar, Nassir
Summary: This paper introduces architectures for next‐generation high throughput satellite (HTS) systems comprising various satellite payload options, ground terminal advances, and scalable system‐level software control and management techniques. It describes a model to estimate aggregate system capacity as a function of radio band, available spectrum, spot beams, waveforms, and payload capability, including antenna size, power, and digital/analog connectivity across various links and availability objectives. This system model has been used to evaluate aggregate capacity of representative Ka‐Band low earth orbit and geosynchronous orbit systems. A system implementation approach is described for next‐generation HTS systems based on widely used Industry standards. Modulation and coding techniques are based on Digital Video Broadcasting – S2 extensions (DVB‐S2X), which comprises spectrally efficient modulation schemes combined with low‐rate codes. Several implementation technologies are analyzed related to configurable onboard payload and ground‐based, software‐defined resource control and management, key enablers of next‐generation HTS systems. Basic architectural building blocks are introduced for design of end‐to‐end systems across low earth orbit, medium earth orbit, and geosynchronous orbit satellite constellations, with and without onboard processing and inter‐satellite links, and including several efficient scenarios to achieve lossless handovers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents a model to estimate aggregate system capacity as a function of radio band, available spectrum, spot beams, waveforms, and payload capability comprising antenna size, power, and digital/analog connectivity across various links and availability objectives for next‐generation high throughput satellite systems. This paper presents architectural building blocks for next‐generation high throughput satellite systems using low earth, medium earth, and geosynchronous orbit satellite constellations, with and without onboard processing and inter‐satellite links. This paper describes a system implementation approach using industry standards such as DVB‐S2X and 4G LTE.